Development of Mobile Application Framework Based on Competency-Based Education for Technical and Vocational Education - Abdul Rahman, Khairul Anuar; Abdul Jalil, Norazwani; M.Arsada, Mohd Azhar; Hashim, Suhaizal; Rahim , Mohd Bekri; Yunus, Faizal Amin Nur; Razali, Nizamuddin; Ismail, Mohd Erfy (Journal of Technical Education and Training, 2021)
The purpose of this study was done to develop a mobile application framework based on Competency Based Education (CBE) in Technical and Vocational Education. CBE approach in teaching and learning should be applied because these approach is suitable for the skill-based education. In technological advancement, mobile application approach causes student have their own control in teaching and learning, so that it can be implemented seamlessly and more effectively. This research had been carried out is a qualitative method that has gone through three phases to get a framework for the mobile app based on CBE. The instruments used are structured interview and evaluators' reliability review form. The study sample consisted of 6 experts both in CBE and technology for the interview session and 3 experts in TVET for reliability data verification. The raw data obtained from the interviews has gone through thematic analysis process using Atlas.ti software. The results, 36 items identified as characteristics of CBE in the mobile application with average Cohen Kappa Index Approval coefficient was 0.9 indicating a very good reliability scale. The findings of this study consists 33 items with seven constructs approved after the inter-rater reliability among the expert. Implication from this research could be used as guidance in the development of instructional mobile application, particularly in the Technical and Vocational Education and as an instrument for evaluating existing instructional mobile applications.